PENGARUH KOMPETENSI TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) TERHADAP INTEGRATION INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN EDUCATION PADA GURU DI MADRATSAH IBTIDAIYAH - Rifqotul Jannah; Ika Ratih Sulistiani; Mohammad Afifulloh (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The incorporation of thecnilogy in the world of education makes one of the learning models applied in learning. TPACK is a theoretical framework that can be used as a learning model by combining three main components, namely technology, pedagogy, and content. So that teachers are able to collaborate between TPACK and ICT in the learning process. This research is a quantitative research using survey method. The variables in this study include Technological Pedagogical and Content Knowledge (independent variable) and Integration Information and Communication Technology In Education (dependent variable). The sample in this study were 35 teachers of MI Tarbiyatul Huda and MINU Hidayatul Mubtadiin. the researcher took the data by using two questionnaires on each variable. The data analysis technique in this study uses simple linear regression analysis which aims to determine whether there is an effect of TPACK on Integration ICT In Education. All calculations used the SPSS_25 program. Based on the results of the simple linear regression analysis technique, the significance value of Sig. 0.002 < probability 0.05(5%). The results of this study indicate that there is an effect of the two variables. Keywords: TPACK, ICT, Education.